Study from antimicrobial and DNA-binding activities of alkaloids from the leaves of ruta angustifolia (L.) pers - Laina Zarisa binti Mohd Kamal (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2013)
Significant finding of Rutaceae alkaloids in search of new drugs have led to an important strategy to overcome the problems of resistance and side effects associated with conventional antibiotics. In this study, leaves of the plant Ruta angustifolia (L.) Pers. was extracted and fractionated by using column chromatography. Through bioassay-guided isolation, combined fraction of R33 and R48, fraction RC-8 and Rd-10 yielded a total of three antimicrobial active alkaloids. These isolated alkaloids were then identified by means of Thin Layer Chromatography profile, melting point and maximum wavelength for UV absorption in methanol (UVλ max-MeOH) in comparison with authentic alkaloids. The identification was further confirmed by 1H NMR and 13C NMR spectroscopic data and was characterized as acridone, furoquinoline and 4-quinolone so named arborinine, skimmianine and graveoline respectively. The antimicrobial activites of arborinine and graveoline were tested against Staphylococcus aureus, Enterococcus fecalis, Helicobacter pylori, Escherichia coli, Pseudomonas aeruginosa and Candida albicans of ATCC strains. Broth microdilution assay of both alkaloids gave Minimum Inhibitory Concentration (MIC) values ranging from 250 µg/ml to 1000 µg/ml. Minimum Bactericidal Concentration (MBC) values were recorded at 1000 µg/ml and more than 1000 µg/ml. The MIC and MBC of the compounds was compared with that of the standard antibiotics namely norfloxacin, ciprofloxacin, vancomycin, erythromycin and ketoconazole. Antibacterial combination effects of graveoline with erythromycin or vancomycin were studied against S. aureus, E. fecalis and E. coli by means of Fractional Inhibitory Concentration (FIC) index. All the tested combination resulted in additive effects with FIC index ranged from 0.75 to 1.02. Antifungal combination effects of arborinine and ketoconazole was experimented against C. albicans and showed synergistic interaction with FIC index of 0.5. Bacterial DNA-binding properties of the three alkaloids were investigated against double-stranded DNA with various restriction enzymes. The investigation revealed that these three alkaloids mostly affect the cleavage activity of the restriction enzymes which contains 5'-TpA sequence rather than 5'-ApT sequence in their recognition pattern and potential crosslink sites under UV exposure. These isolated alkaloids were screened to possess antimicrobial activity through DNA synthesis inbition mechanism and might need to combine with other agent to enhance its inhibitory effects.